2011
DOI: 10.1111/j.1365-2230.2011.04186.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor gene polymorphisms and risk for androgenetic alopecia: a meta-analysis

Abstract: Our meta-analysis suggests that the G allele of AR StuI polymorphism might be a potential risk factor for AGA, especially in white populations. However, we did not find any obvious association of the CAG and GGC triplet-repeat polymorphisms of the AR gene with risk for AGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 27 publications
1
53
1
Order By: Relevance
“…Following the same line of thought that led to the investigation of a potential link between CAGn and 2D:4D (17), numerous studies looked into the link between CAGn and these conditions. Recent meta-analyses of these studies show that evidence for such a link is at best tentative for prostate cancer and absent for the other three (4143). …”
Section: Discussionmentioning
confidence: 99%
“…Following the same line of thought that led to the investigation of a potential link between CAGn and 2D:4D (17), numerous studies looked into the link between CAGn and these conditions. Recent meta-analyses of these studies show that evidence for such a link is at best tentative for prostate cancer and absent for the other three (4143). …”
Section: Discussionmentioning
confidence: 99%
“…All four components could play a role and, more broadly, baldness may represent a proxy of the overall androgen status considered as the result of all these components. For example, a meta-analysis (Zhuo et al, 2012) found an association between androgenic alopecia and a polymorphism of the androgen receptor gene (locus Xq11-q12), suggesting that baldness is also related to individual sensitivity to androgens. Indeed there are important ethnic differences both in the androgen status and in the incidence of testicular cancer further suggesting that there is a complex interplay between the different components.…”
Section: Discussionmentioning
confidence: 99%
“…One synonymous variant, E213 (rs6152G>A), is located between the two polymorphic CAG and GGN tracts. This variant has been linked to androgenetic alopecia in Caucasian populations, where the minor allele (rs6152A) in these populations was associated with a decreased risk (18)(19)(20). In a previous EMAS analysis, carriers of the rs6152A variant were also found to have significantly lower estradiol levels than those with rs6152G (21).…”
Section: Introductionmentioning
confidence: 94%